An Expanding mercantile circuit in the South Atlantic in the late colonial period (1796-1821) - De Moura, Denise A. Soares [UNESP] (My University, 2015)
This text discusses the development of the mercantile links between port cities on the coast of the Center and South of Portuguese America and the provinces of the River Plate estuary in the period from 1796 to 1821. To achieve this, data were gathered about the records kept of ships entering and leaving the port of Montevideo, about the exportation and importation charts produced by the Board of Trade at Rio de Janeiro and the official correspondence written by the Governor of the São Paulo captaincy. Various types of foodstuffs were exchanged in this mercantile circuit. The liberalization of the Atlantic economy in this period strengthened the trade links that had existed between Portuguese America and the provinces of the River Plate region since the seventeenth century.
Keywords: Colonial merchandise; Iberian Atlantic; River plate; Trade; Trade network